Comparative Analysis of Different ELISA Methods for the Serodiagnosis of Przhevalskiana silenus Infestation in Goats - Liaqat, Sadia; Qayyum, Mazhar; Celik, Figen; Simsek, Sami; Ahmad, Faheem; Zhang, Xiaocheng; Cao, Jianping (Mdpi, 2023)
Simple Summary Warble fly is a globally important pest of domesticated and wild animals in the northern hemisphere. Goat warble fly infestation (GWFI), triggered by the obligatory parasite Przhevalskiana silenus larvae, has detrimental consequences for livestock. GWFI is usually not accurately detected by the traditional methods of detection. This study aimed to identify the best diagnostic method for the early detection of GWFI by comparing three enzyme-linked immunosorbent assay (ELISA) methods using Hypoderma purified antigen (Hypodermin C), the crude antigen of P. silenus, and a commercially available hypodermosis ELISA kit, in the Pothwar region of Punjab, Pakistan. The sampling was carried out in 1000 goats, randomly selected from four districts (Rawalpindi, Attock, Jhelum, and Attock) of the Pothwar region, Punjab Pakistan. The seroprevalence, determined via ELISA with the crude P. silenus antigen, hypodermin C (HyC) antigen, and the commercial ELISA kit, was 17%, 15.5%, and 18.6%, respectively. Cohen's Kappa test confirmed that all the three assays could be employed for the early detection of GWFI, while an indirect crude P. silenus antigen ELISA was more sensitive and accurate. Przhevalskiana silenus (warble fly) grubs cause myiasis in goats, in mountainous and semi-mountainous areas and different regions in Pakistan, and cause substantial losses to livestock. The palpation method for detecting warble flies generally neglects the infestation intensity; therefore, the development of a reliable and efficient diagnostic technique is extremely necessary. This study compared three indirect enzyme-linked immunosorbent assay (ELISA) methods for detecting anti-P. silenus antibodies using the hypodermin C (HyC) purified from Hypoderma spp. Larvae collected in cattle (local isolate, Microbiology Laboratory, PMAS-Arid Agriculture University, Rawalpindi), the crude antigen from the first instar stage of P. silenus, and a commercial Bovine Hypodermosis Antibody ELISA kit (IDEXX Laboratory), for accurately estimating the seroprevalence of goat warble fly infestation (GWFI) in the Pothwar plateau, Punjab, Pakistan. The ELISA with the crude antigen of P. silenus proved very sensitive and specific, 91% and 93%, respectively. The optical density exhibited a monthly variation, and the antibody titer began increasing from June, continually increased from July to December, and gradually decreased thereafter until March. The study confirmed the endemic status of GWFI in the Pothwar region and identified that ELISA based on the crude antigen of P. silenus was a more sensitive and specific immunodiagnostic method for determining seroprevalence, and could be employed for initiating nationwide eradication campaigns.
Keywords: hypodermosis; myiasis; immunodiagnosis; indirect ELISA; Przhevalskiana silenus; warble fly; goat warble fly infestation; Pakistan